PATHWAYS TO ENHANCING THE EFFICIENCY OF BUSINESS MANAGEMENT MECHANISMS IN HEALTHCARE - Letunovska, Nataliia; Khomenko, Liliia; Chvankin, Yevhen (Socio-economic relations in the digital society, 2025)
The article presents an assessment of the operational efficiency of the Sumy Regional Blood Service Center and the Kharkiv Regional Blood Service Center. The analysis was carried out considering key performance indicators of the institutions, encompassing economic, managerial, informational, technological, and social aspects. Based on the results of the efficiency evaluation of these blood service enterprises, a system of measures was developed and proposed to enhance the performance of the analyzed centres. These measures were structured according to the main determinants of functioning: managerial, informational, security-related, and economic, and aligned with modern requirements for business processes in the blood service sector, particularly at the stages of collection, processing, storage, quarantine, and distribution of blood components. The selection and prioritization of the recommended measures were based on consultations with key target audiences, including new and regular donors, healthcare institutions, and blood centre staff, as well as taking into account the components of the marketing mix (product, price, promotion, place, people, processes, physical environment). The development of proposals also incorporated comparative analysis data and the experience of leading countries in the field of blood donation, which made it possible to integrate best international practices into the national context. Special attention was given to identifying stakeholders, including the Ministry of Health of Ukraine, the Ministry of Energy, the Ministry of Digital Transformation, the Ministry of Education and Science, other government bodies, healthcare institutions, regional enterprises, associations and NGOs, media outlets, advertising and marketing agencies. The proposed measures aim to address current challenges in the blood supply sector, improve population access to safe, high-quality blood components, and enhance overall satisfaction with blood services. Implementation of these initiatives will significantly increase the competitiveness of blood service enterprises in the national healthcare market.